In situ formation of spherical MoS2 nanoparticles for ultra-low friction. Issue 42 (23rd October 2018) - Hou, Kaiming; Han, Minmin; Liu, Xiaohong; Wang, Jinqing; He, Yezeng; Yang, Shengrong
Abstract : The spherical MoS2 nanoparticles formed through structural evolution under the induction of shear stress can lead to ultra-low friction. Abstract : The motion resistance and energy dissipation of rolling friction are much lower than those of sliding friction at the macroscale. But at the microscale, the impact of rolling on friction remains an open question. Here, we show that spherical MoS2 nanoparticles can be formed in situ at a friction interface by scrolling and wrapping MoS2 nanosheets under the induction of a reciprocating shear stress, when an MoS2 coating constructed from loosely stacked nanosheets is tested in a vacuum of 3.5 × 10 −3 Pa. An ultra-low friction state can be readily realized with friction coefficients of 0.004–0.006, which are one order of magnitude lower than that of a pulse laser deposited MoS2 coating without nanoparticles formed in a friction process. Accordingly, the spherical nanoparticles are highlighted as the key factor in the ultra-low friction. Classical molecular dynamics simulations further reveal that the motion mode of the MoS2 nanoparticle is stress-dependent. This finding confirms access to ultra-low friction by introducing rolling friction based on the microstructural evolution of the coating.